Implementasi Sistem Penyampaian Jasa Pendidikan di SMKN 1 Cijulang - Rini Indah Sari; Irfan Apandi; Anja Sugiarti; Pipin Pitriyani; Irpan Ilmi (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2023)
The educational service delivery system is part one of marketing management. Marketing management for educational institutions, especially madrasas, is needed in line with the increasingly competitive competition between schools. Marketing is needed by educational institutions in building a positive image. If the institution has a good view in the eyes of the community, it is likely that it will be easier to overcome competition. The purpose of this research is to describe the description of the implementation of the education service delivery system. This research is a qualitative research, with data collection methods, namely: observation, interviews, documentation. The results of the study show that the service delivery system or education marketing carried out by SMKN 1Cijulang is by using internal marketing, external marketing and interactive marketing.